Effect of Cow Dung as Organic Manure on the Productivity of Cajanus cajan (L.) Millsp (Pigeon pea) - Oktavius Yoseph Tuta Mago; Yohanes Nong Bunga (Mangifera Edu, 2020)
Cajanus cajan (L.) Millsp is a local plant which not fully utilized by people in Sikka. This plant has a high nutrient content besides a potential of traditional medicine. This research is aimed to examine the effect of organic fertilizer on Cajanus cajan (L.) Millsp productivity. This research was carried out in Geliting village of Sikka District from May to December 2019. Cow dung and agricultural by-product were used as organic fertilizers. Before applied to the plant, these ingredients were mixed and anaerobically fermented in 30 days. The fertilizer dosage are as follows, 0 kg/m2 (control), 0,5 kg/m2, 1 kg/m2, 1,5 kg/m2, 2 kg/m2, and 2,5 kg/m2. Randomized Block Design was used and examined variables were the flowering time, number of pods, and wet weight of seed. The result showed that there was no effect of organic fertilizer on Cajanus cajan (L.) Millsp productivity.